The Impact of Year of Study, Gender and Academic Performance on Students’ Perception on Academic Advising in Kenyan Universities - Muola, James Matee; Maithya, Redempta; Migosi, Joash A. (My University, 2013)
A sample of 187 university students (53, 41 and 93 first, second and third year respectively) participated in this study. No significant relationship (r = 0.138) was found between the rate at which students seek academic advising and their perception on the programme. The findings showed that the perception on academic advising of students in different years of study is significantly (P < 0.05) different. The perception on academic advising of male and female students was not statistically significant (P > 0.5). A positive and significant (r = 0.256; P < 0.01) relationship was reported between academic performance and students’ perception on academic advising. It was concluded that ways of sustaining and improving students image on academic advising be put in place.